(untitled) (Homoeopathy for All, 2024)
Homoeopathy, a system of alternative medicine founded by Samuel Hahnemann in the late 18th century, is gaining traction as a viable first-line treatment option worldwide. This article examines the foundational principles, clinical efficacy, and increasing acceptance of homoeopathy within modern healthcare, especially in primary care contexts.